UK Shale Gas – Hype, Reality and Difficult Questions - Rogers, H (Oxford Institute for Energy Studies, 2013)
The shale gas phenomenon has transformed the US from prospective LNG importer to the current expectation of it becoming a major LNG exporter. In the UK the recent upgraded estimates by the British Geological Society of shale gas resources in the north of England have unleashed a wave of speculation in the media which includes an anticipation of lower prices and eliminating the need for natural gas imports. Drawing on US data, this Comment seeks to highlight the practicalities to be faced in developing the UK’s shale gas resources and addresses the drilling intensity and timescale required to achieve meaningful levels of production. It is deemed unlikely that UK shale gas development would have a discernible effect of wholesale gas prices. Whilst the increased fiscal contribution and balance of payments impact of shale gas would be beneficial at a national level, the real challenge will be that of gaining public acceptance in the locales where shale gas development will have a visual and traffic impact during the drilling phase. In the event that exploratory activities confirm the viability of UK shale gas plays the industry will need to engage in a public acceptance campaign based mainly on an offer of training, jobs and local economic stimulus if it is to succeed.